Evaluasi Tingkat Kepuasan Masyarakat terhadap Pelayanan Publik di Desa Parigi Kabupaten Serang - Wahyudi, Heru; Ardiyansah, Ardiyansah; Shafira, Albarika Kharisma (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka, 2025)
This study aims to evaluate the level of public satisfaction with public services in Parigi Village, Cikande District, in 2024, using the SERVQUAL model, which includes the dimensions of Tangibility, Reliability, Responsiveness, Assurance, and Empathy. The research employs a quantitative survey approach, involving 370 respondents selected through random sampling. The findings indicate that Tangibility and Assurance have the highest satisfaction levels, while Responsiveness has the lowest satisfaction level, highlighting the need for improvement in service responsiveness and speed. Other factors contributing to public dissatisfaction include a lack of service personnel, limited accessibility, and inconsistent information delivery. Therefore, recommendations for improvement focus on enhancing human resource capacity, optimizing digital service technology, and standardizing service procedures to ensure greater effectiveness, efficiency, and transparency